PENGARUH PENGAWASAN ATASAN MELEKAT TERHADAP KINERJA GURU PAUD DENGAN MEDIASI PEMBELAJARAN ORGANISASI (Studi Empiris Pada Guru Pendidikan Anak Usia Dini di Kabupaten Serang) - Vera Maria; Agus Tiar (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this study was to determine the effect of inherent supervisor supervision on the performance of PAUD teachers in Serang Regency by mediating organizational learning. Optimization of early childhood education can be achieved by high-performing PAUD teachers so that learning activities through play activities can carry out optimal targets. The research method uses quantitative methods with causal design. Sampling technique using purposive sampling with the number of samples obtained by 44 respondents. Data analysis using multiple linear regression and multiple test. Partial hypothesis testing, it is known that supervisor supervision is inherent and organizational learning has a positive effect on the performance of PAUD teachers partially. While the supervision of inherent superiors has no effect on organizational learning. Hypothesis testing with the mediating effect, it is known that organizational learning mediates the influence of supervisor supervision attached to the performance of PAUD teachers in Serang District